Resposta :
Explicação passo a passo:
a2 6 2 [tex]\frac{1}{2} +\frac{5}{6} =\frac{3}{6} +\frac{5}{6} =\frac{8}{6} =1\frac{2}{6}[/tex]
1 3 3
1 1 6
b[tex]\frac{3}{2} -\frac{1}{2} =\frac{2}{2} =1[/tex]
c6 3 2
3 3 3
1 1 6 [tex]\frac{5}{6} -\frac{1}{3} =\frac{5}{6} -\frac{2}{6} =\frac{5}{6}[/tex]
d[tex]\frac{1}{3} +\frac{5}{6} =\frac{2}{6} +\frac{5}{6} =\frac{7}{6} =1\frac{1}{6}[/tex]
e 5 10 2
5 5 5[tex]\frac{2}{5} -\frac{3}{10} =\frac{4}{10} -\frac{3}{10} =\frac{1}{10}[/tex]
1 1 10
f 5 6 2
5 3 3
5 1 5
1 1 30